Journalism teaching and experiential learning - Kartveit, Kate (Žurnalistikos tyrimai, 2009)
TV-journalism can never be thought successfully entirely on a theoretical basis. The students must experience the professions challenges and difficulties by exercising and experiencing the TV-journalistic methods, TV-tools and TVaesthetics in practice in order to achieve skills within TV-journalism. The article discusses how Kolb’s learning circle successfully provides a pedagogic approach in practical journalism learning and teaching. Kolb experiential learning theory says that ideally the learning process represents a learning cycle or spiral where the learner touches four bases in process, that means a cycle of experiencing, reflecting, thinking, and acting. Kolb describes four different learning styles or learning preferences. This refers to four different ways of experiencing the learning process. Every learner has a preference to learn in different ways andthe learning circle offers the learners to fulfil the learning process no matter what starting point the learner prefers. This approach focuses on journalism training as growing a person from the inside, whereas conventional teaching and training is the transfer of capability into a person from the outside.Keywords: coaching, conventional learning, David A. Kolb, Experience Based Learning Systems, Experiential Learning Theory, International TV-program, journalism studies, learning cycle, learning process, pedagogical approach, TV-journalism.p>